Health System Performance for Multimorbid Cardiometabolic Disease in India: A Population-Based Cross-Sectional Study. Issue 1 (31st January 2022) - Geldsetzer, Pascal; De Neve, Jan-Walter; Mohan, Viswanathan; Prabhakaran, Dorairaj; Roy, Ambuj; Tandon, Nikhil; Davies, Justine I.; Vollmer, Sebastian; Bärnighausen, Till; Prenissl, Jonas
Background: The prevalence of multimorbidity in low- and middle-income countries (LMICs) is thought to be rising rapidly. Research on the state of healthcare for multimorbidity in LMICs is needed to provide an impetus for integration of care across conditions, a baseline to monitor progress, and information for targeting of interventions to those most in need. Focusing on multimorbid cardiometabolic disease in India, this study thus aimed to determine 1) the proportion of adults with co-morbid diabetes and hypertension who successfully completed each step of the chronic disease care continuum from diagnosis to control for both conditions, and 2) how having additional cardiovascular disease (CVD) risk factors is associated with health system performance along the care continuum for diabetes, hypertension, and co-morbid diabetes and hypertension. Methods: Using a nationally representative household survey carried out in 2015 and 2016 among women aged 15–49 years and men aged 15–54 years, we created a 'cascade of care' for diabetes, hypertension, and co-morbid diabetes and hypertension by determining the proportion of those with the condition who had been diagnosed, were on treatment, and achieved control. We used Poisson regression with a robust error structure to estimate how having additional cardiovascular disease (CVD) risk factors (diabetes, hypertension, current smoking, and obesity) was associated with reaching each cascade step for diabetes, hypertension, and co-morbid diabetes and hypertension. Findings: Seven hundred thirty-four thousand seven hundred ninety-four adults were included in the analysis. Among individuals with co-morbid diabetes and hypertension, 28·8% (95% CI, 26·7%–31·0%), 16·1% (95% CI, 14·4%–17·9%), and 3·7% (95% CI, 2·8%–4·9%) – with these proportions varying between states by a factor of 4·8, 7·9, and 56·8 – were aware, treated, and achieved control of both conditions, respectively. Men, adults with lower household wealth, and those living in rural areas were less likely to reach each cascade step. Having additional CVD risk factors generally did not increase the probability of reaching each cascade step for diabetes, hypertension, and co-morbid diabetes and hypertension, except that having concurrent diabetes increased the probability of successfully transitioning through the hypertension care cascade. Interpretation: While varying widely between states and population groups, health system performance for co-morbid diabetes and hypertension is generally low in India, and there appears to be little integration of care across CVD risk factors. Funding: European Research Council.